Sosialisasi CPPOB pada Kelompok Wanita Tani di Desa Lendang Nangka untuk Menunjang Desa Wisata - Rina; Meikapasa, Ni Wayan Putu; Isnain , Fuad Sauqi; Naufali, Muhammad Nizhar (Insan Kreasi Media, 2022)
One of the important things in organizing a tourist village is the availability of typical snacks or processed food products that can be used as souvenirs for tourists. Especially in Lendang Nangka as one of famous tourist village. The Women Farmers Group (KWT) plays an important role in supporting the availability of processed food products for tourist villages. One of the problems faced by KWT in this village is the limited information regarding good processing of processed food (CPPOB) or Good Manufacturing Process (GMP) so that the products cannot be used as souvenirs. The methods used in the implementation of Community Service (PkM) are surveys, presentations and discussions. The expected output of this activity is that this KWT able to implement CPPOB properly so that it can produce healthy, safe and high quality souvenir products in order to support the existence of the Lendang Nangka tourist village. Through this community service, KWT members become more aware of the importance of implementing CPPOB and easily applied it when processing souvenir products.